Management of the alien invasive red king crab Integrating natural and social science perspectives - Falk-Petersen, Jannike (University of Tromsø, 2012)
The papers of this thesis are not available in Munin: 1. Falk-Petersen, J, Bøhn, T. and Sandlund, O.T.: 'On the numerous concepts in invasion biology', Biological Invasions (2006), 8: 1409-1424. Available at http://dx.doi.org/10.1007/s10530-005-0710-6 2. Armstrong, C.W. and Falk-Petersen, J.: Habitat-fisheries interactions : a missing link?', ICES Journal of Marine Science (2008), 65: 817-821. Available at http://dx.doi.org/10.1093/icesjms/fsn092 3. Falk-Petersen, J., Renaud, P. and Anisimova, N.: 'Establishment and ecosystem effects of the alien invasive red king crab in the Barents Sea', ICES Journal of Marine Science (2011), 68 (3): 479-488. Available at http://dx.doi.org/10.1093/icesjms/fsq192 4. Falk-Petersen, J. and Armstrong, C.: 'To have one’s cake and eat it : managing the alien invasive red king crab stock' (submitted manuscript). 5. Falk-Petersen, J.: 'Option lost or opportunity gained? Perceptions on the Barents Sea red king crab invasion', (submitted manuscript). The red king crab (Paralithodes camtschaticus) is a highly valuable resource that also represents a potential threat since it is an alien invasive species in the Barents Sea ecosystem. This thesis explores the use of different interdisciplinary frameworks to analyse how ecological, social and economic concerns could be accounted for in deciding on how the king crab should be managed in the Norwegian part of the Barents Sea. Clarification of terminology used in invasion biology and systematisation of ecological information in order to establish the ecological knowledge base for management forms the basis for further analysis. Bio-economic modelling and discourse analysis are used to explore how uncertainty and the range of services the ecosystem provides can be incorporated in management. Finally the use of ecosystem service frameworks to integrate ecosystem and social science research in ecosystem based management is discussed. The ecological review revealed numerous knowledge gaps in our understanding of how the king crab interacts with ...